Percepatan Pendaftaran Tanah Yang Belum Memiliki Sertifikat Hak Milik Untuk Meningkatkan Ekonomi Dan Pencegahan Konflik Di Desa Marindal-I - Harahap, Anwar Sadat; Siregar, Disna Anum; Sembiring, Zamalludin; Putra, Andhika Dharma; Alawiyah, Safty; Harahap, Irma Tasya; Humairoh, Lathifah (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2024)
Mitra consists of 271 heads of families out of 685 heads of families in Marindal-I Village who still own land with land ownership status in the form of a Certificate signed by the village head or in the form of a sale and purchase letter and others in the form of a Land Certificate signed by the Patumbak District Head. and several plots of inherited land in Marindal-I Village, it turns out that their ownership rights have not been divided by other heirs. As a result, some heirs cannot use the land certificate of the inherited land they are part of as collateral in borrowing money from the bank for business capital. Method of implementing assistance methods for communities who do not yet have a Certificate of Ownership Rights together with the Team with staff from the Marindal-I Village Head's office to take care of land registration and carry out training and assistance to the community and partners regarding procedures for registering land with the BPN Office as regulated in statutory regulations applicable. The results obtained were land registration at the Deli Serdang Regency BPN Office of as many as 43 families out of the 97 targeted, carrying out training in the process of managing and completing land registration files and forming Kelompok Masyarakat Pendaftar Tanah (KMPT) whose main task is to assist in the land registration process continuously and continuously.